Eating behaviors related to nutritional status among adolescents: a cross-sectional study - Eka Oktavianto; I Made Moh. Yanuar Saifudin; Suryati Suryati; Supriyadi Supriyadi; Niken Setyaningrum (International Journal of Public Health Science (IJPHS), 2023)
Adolescents are still prone to the issues of under and overeating. Eating behaviors are one factor that affects adolescents' nutritional status. This study aimed to look at the relationship between adolescents' eating behaviors and nutritional status. The cross-sectional study was conducted between September and November 2022. The self-evaluation instruments were completed by one hundred seventy-two individuals. Spearman-rank correlation analyses were performed. The findings showed that 84 (48.8%) adolescents had normal nutritional status, compared to 73 (42.4%) adolescents who engaged in low-risk eating. Nutritional status and eating behaviors were substantially associated (r=0.41, p=0.03). This research shows that individuals with bad eating behaviors have a greater risk of experiencing nutritional disorders. This study has certain limitations, such as the sample's composition of adolescents from a particular Yogyakarta area, which restricts the applicability of our findings to other communities. A longitudinal study is required to ascertain the cause-effect relationship between eating behavior and nutritional status. Accordingly, the cooperation of various parties is needed to increase adolescent knowledge about the importance of optimal nutrition during the growth period and understanding related to a healthy diet. It is hoped that there will be further research on other factors that influence the nutritional status of adolescents.